2021
DOI: 10.3390/s21186183
|View full text |Cite
|
Sign up to set email alerts
|

Early Warning Systems for COVID-19 Infections Based on Low-Cost Indoor Air-Quality Sensors and LPWANs

Abstract: During the last two years, the COVID-19 pandemic continues to wreak havoc in many areas of the world, as the infection spreads through person-to-person contact. Transmission and prognosis, once infected, are potentially influenced by many factors, including indoor air pollution. Particulate Matter (PM) is a complex mixture of solid and/or liquid particles suspended in the air that can vary in size, shape, and composition and recent scientific work correlate this index with a considerable risk of COVID-19 infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…As the presence of indoor PM and NO 2 may indicate presence of SARS-CoV-2, this could be monitored with inexpensive sensors and reduced with air purifiers ( Kaliszewski et al, 2020 ; Li et al, 2020a ; Liu et al, 2021a ; Peladarinos et al, 2021 ). High efficiency particulate air filters (HEPA) and fine filters have been reported to disinfect 83% and 54% SARS-CoV-2 containing aerosols, respectively, and have a high filtration efficiency for 0.3 µm - 10 µm particles ( Zhang, 2020 ; Zhao et al, 2020a ).…”
Section: Indoor Airmentioning
confidence: 99%
“…As the presence of indoor PM and NO 2 may indicate presence of SARS-CoV-2, this could be monitored with inexpensive sensors and reduced with air purifiers ( Kaliszewski et al, 2020 ; Li et al, 2020a ; Liu et al, 2021a ; Peladarinos et al, 2021 ). High efficiency particulate air filters (HEPA) and fine filters have been reported to disinfect 83% and 54% SARS-CoV-2 containing aerosols, respectively, and have a high filtration efficiency for 0.3 µm - 10 µm particles ( Zhang, 2020 ; Zhao et al, 2020a ).…”
Section: Indoor Airmentioning
confidence: 99%
“…In addition, a quick alert system was introduced to minimize damage to the indoor air quality [31]. Peladarinos et al ( 2021) developed an early warning system for COVID-19 infection using an air quality measurement system [32]. The developed server operates a web program to manage the air quality measurement devices and measurement data of sixteen air quality items.…”
Section: Software Process Of Multi-item Air Quality Monitoring Systemmentioning
confidence: 99%
“…As can be noted, in the literature review described above, no automated systems were found for monitoring, control and decision-making, integrating early warning systems, information systems that monitor disaster risk levels, systems for health care management in hospitals, or for autonomous movement for people with visual or hearing impairment in enclosed spaces and in public passenger transport, except for some combinations, as in [ 53 ]. In that instance, they combined EWS and IoT for the development of sensor-based wide area networks to measure levels of solid particles in the air and determine air pollution.…”
Section: Introductionmentioning
confidence: 99%